Forced Displacement in Conflict Scenarios : Ethics and Human Rights Perspectives (2022)
This book reflects fruitful exchanges, debates, and collaborations in different times and settings, highlighting the relevance of interdisciplinary work, open to broadening the horizon of knowledge through multiple perspectives and the always different, and therefore, enriching view from the other. It is a testimony of the collaborative work developed from an ethical and evidence-based perspective, fundamental characteristics of the bioethical view that encouraged us to publish it.